Needs of Terminally ill Patients and their Families: An Experience with Fifty-three Patients Attending a Newly Organized Palliative Care Service in Bangladesh (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Objective: To identify the needed care of the terminally ill patients and their families in Bangladesh Design: Retrospective, descriptive cross-sectional study Setting: Out Patient Consultation, referred admitted patients and home care visits by the same palliative care team of Bangabandhu Sheikh Mujib Medical University (BSMMU) Participants: 53 terminally ill cancer patients registered with the palliative care service of BSMMU Results: Age range of 22 to 80 years, mostly from middle to poor class. Most of the patients needed relief from pain, anxiety, sleeplessness and constipation along with other symptom relief. Major concern of patients was financial whereas major concern of family members was not to inform the patient of the disease status.. Preferred site of care was at home when uncertainty about the disease status was reduced. Conclusion: even if a ‘good life' is not possible for all the people of Bangladesh, ‘a good death for most of the patients suffering from incurable diseases can be an affordable reality. Key words: need, symptom assessment, palliative care, Bangladesh   Journal of BSA, Vol. 19, No. 1 & 2, 2006 p.38-43